Pengaruh Fungsi Sikap Pelanggan terhadap Jangka Waktu Pembelian Kembali Telepon Selular Merek Nokia di Surabaya - Astuti, Sri Wahjuni; Wulandari, Retno Sih (Jurnal Widya Manajemen & Akuntansi, 2007)
The tendency of customer to repurchase the new product has been change. Customers often replace the previous product with new ones even though the function is still good. Customer attitude, which is made by the function of knowledge, value-expression, social judgement, and benefit, influences the lime period to repurchase the new product. This research conduct for the Nokia selluler phone customer in Surabaya. Sampling method was accidental sampling. Statistical analysis with logistic regression. Research conclusion was attitude functions significantly affect the time period to repurchase new product.